Compositions and methods for removal of per- and polyfluoroalkyl substances (pfas) - Zhao, Dongye; Liu, Wen; Li, Fan; Tianyuan Xu; Yangmo Zhu; Duan, Jun; Zongsu Wei (2021)
The invention relates to composite compositions including a carbonaceous material and a photocatalyst. The invention includes compositions and various methods, including methods for removing one or more contaminants from a substance such as air, soil, and water.